Estimation and correlation of salivary thiocyanate levels in healthy and different forms of tobacco users having chronic periodontitis: A cross-sectional biochemical study - C Veena Kalburgi; K Lavanya Naik; M Vijayalaxmi Kokatnur; Shivaraj Warad (Wolters Kluwer Medknow Publications, 2014)
Background: Periodontitis is a common inflammatory disease with complex and multi-factorial origin. Tobacco usage has shown its adverse effect on periodontal health. Various components within saliva not only protect the integrity of oral tissues, but also provide clues to local and systemic diseases and conditions. Salivary thiocyanate (SCN) has been shown to be a chemical indicator in smokers and smokeless tobacco users. Noninvasive nature of salivary testing has made it an attractive and effective alternative to blood and urine testing. Limited studies are there comparing and correlating the salivary SCN levels in smokers with chronic periodontitis (CP). However, no studies show correlation of salivary SCN among gutka chewers with CP. Aims and Objectives: The objective of the following study is to estimate, compare, and correlate the SCN levels in periodontally healthy, CP, smokers with CP and gutka chewers with CP subjects. Materials and Methods: Study includes 120 subjects with age 18-55 years, categorized as periodonally healthy (n = 30), CP (n = 30), smokers (n = 30), and gutka chewers (n = 30) with CP. Required clinical parameters such as gingival index, probing depth and clinical attachment loss were recorded and salivary SCN levels were estimated through ultraviolet-spectrophotometer. Results: Mean salivary SCN level were shown to be higher among smokers and gutka chewers with CP as compared to healthy and CP alone. Conclusion: The present study exhibited the significant increase in salivary SCN levels among smokers and gutka chewers when compared to others, concluding that the analysis of salivary SCN levels could be used as an adjunctive means of diagnosis.